ANALISIS KEBUTUHAN PENGEMBANGAN E-LKPD HYPERCONTENT BERBASIS AI PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Murwani, Sri; Syarifuddin; Riswan Jaenudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the needs of students and teachers in developing E-LKPD Hypercontent AI-Based Social Science Learning in Class V Elementary Schools. Specifically to find out what the learning needs are in class, the need for media and technology, interest in the Natural Appearance Science and Science material. And what are the needs and expectations of students and teachers regarding E-LKPD. So that later it can help create learning that is effective and relevant to the needs and potential of each student. Next, by using descriptive qualitative methods, researchers want to analyze the data that has been obtained in the field. The results after a needs analysis were carried out were that 83% of students and 84% of teachers had various needs in learning. 79% of students and 91% of teachers need learning media, and 79% of students and 81% need technology assistance to support learning and 79% of students and 91% of teachers want E-LKPD in learning. Furthermore, 85% of students and 95% of teachers stated that they supported the development of this E-LKPD. By looking at the results of theneeds analysis, it has indicated that media development can be carried out immediately so that later it can be used by students and teachers to help them in the learning process in the classroom.Keywords: Need analysis, E-LKPD, IPAS, Elementary School